Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3892/etm.2014.1599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neoadjuvant chemotherapy combined with hyperthermic intraperitoneal perfusion chemotherapy on advanced gastric cancer

Abstract: Neoadjuvant and hyperthermic intraperitoneal chemotherapies have been shown to be effective in the treatment of resectable advanced gastric cancer. The aim of the present study was to investigate the clinical efficiency and security of neoadjuvant chemotherapy in combination with hyperthermic intraperitoneal chemotherapy for the treatment of postoperative advanced gastric cancer. A total of 192 patients diagnosed with advanced gastric cancer were randomly divided into the following four groups (n=48 per group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 18 publications
(20 reference statements)
0
30
0
Order By: Relevance
“…One RCT(19) reported a four arm subgroup analysis comprising the effect obtained in patients undergoing or not undergoing neoadjuvant chemotherapy. Two studies(13, 17) reported a third group in which patients underwent gastrectomy+NIC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One RCT(19) reported a four arm subgroup analysis comprising the effect obtained in patients undergoing or not undergoing neoadjuvant chemotherapy. Two studies(13, 17) reported a third group in which patients underwent gastrectomy+NIC.…”
Section: Resultsmentioning
confidence: 99%
“…We did not analyze this group because it met the exclusion criteria for the meta-analysis. Eight studies(6, 1416, 18, 26, 30) reported the use of Mitomycin C (MMC), eight studies(9, 16, 27, 30, 33, 42–44) a combination of MMC with cisplatin 8,12,18,23 or etoposide(25) or cisplatin+etoposide(24, 27, 29), one study(20) cisplatin alone, and another study(19) cisplatin combined with fluorouracil. The studies provided limited data regarding administration of neoadjuvant and adjuvant treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another trial from our institution (1998 to 2001), it was found that when comparing 42 subjects who underwent surgery + HIPEC with 54 subjects who had surgery alone, the 1-, 2-, and 4-year survival rates were more favorable in the HIPEC group, and the peritoneal recurrence was 34.7% vs. 10.3%, in favor of HIPEC [31]. In a study by Cui et al, where 192 AGC patients were randomly divided into the following four groups (control, NAC, HIPEC and combined groups), the results suggested that NAC combined with HIPEC for the treatment of AGC is well tolerated and exhibits improved compliance and efficiency [32]. In another study from our team, with a pool of 80 patients with 40 patients undergoing prophylactic HIPEC while the control group had surgery alone, the results showed that the experimental arm had significant survival benefit with a decrease in peritoneal metastatic rate [33].…”
Section: Prophylactic Hyperthermic Intraperitoneal Chemotherapymentioning
confidence: 99%
“…With the optimization of the comprehensive treatment modality for AGC, the option of combining NAC's tumor down-staging and HIPEC's prophylactic against peritoneal dissemination was explored. In a study by Cui et al, the combination of NAC with HIPEC for the treatment of AGC was well tolerated and exhibited improved compliance and efficiency with survival benefit [18] . In a study by Coccolini et al, prophylactic HIPEC associated to NAC increased the DFS and OS in patients with AGC without carcinomatosis [19] .…”
Section: Introductionmentioning
confidence: 99%